2003
DOI: 10.1002/mrm.10677
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive approach for correction of motion and distortion in diffusion‐weighted MRI

Abstract: Patient motion and image distortion induced by eddy currents cause artifacts in maps of diffusion parameters computed from diffusion-weighted (DW) images. A novel and comprehensive approach to correct for spatial misalignment of DW imaging (DWI) volumes acquired with different strengths and orientations of the diffusion sensitizing gradients is presented. This approach uses a mutual information-based registration technique and a spatial transformation model containing parameters that correct for eddy current-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
444
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(452 citation statements)
references
References 19 publications
3
444
1
Order By: Relevance
“…Eddy-current distortions and subject motion in the diffusion-weighted images were removed by a 14-parameter constrained nonlinear coregistration based on the expected pattern of eddy-current distortions given the phase-encode direction of the acquired data (65).…”
Section: Methodsmentioning
confidence: 99%
“…Eddy-current distortions and subject motion in the diffusion-weighted images were removed by a 14-parameter constrained nonlinear coregistration based on the expected pattern of eddy-current distortions given the phase-encode direction of the acquired data (65).…”
Section: Methodsmentioning
confidence: 99%
“…Most previous studies applied their EC correction scheme on phantoms or on individual subjects (14,(19)(20)(21)(22)(23)(24)(25)(26)(37)(38)(39). However, interindividual comparisons of EC distortions in a group of healthy subjects have not yet been published.…”
Section: Analysis I: Evaluation Of Affine Whole-brain Ec Effectsmentioning
confidence: 99%
“…Beside the time dependence of the EC field, also secondorder, spatial EC-field components could lead to nonlinear EC distortions (20). A recent study showed that secondorder EC distortions could be of the same order of magnitude as first-order effects (40).…”
Section: Analysis Ii: Slicewise and Whole-brain Registrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This step also compensated for motion during the DWI acquisition. The corresponding gradient directions were adapted accordingly (23)(24)(25). The tensor was then estimated from the aligned data using the "analyzedti" function from Camino (26).…”
Section: Preprocessingmentioning
confidence: 99%